Success in selling : developing a world-class sales ecosystem - Sisakhti, Reza (ATD Press, 2016)
This book presents research on key trends reshaping today's sales profession and introduces the new ATD World-Class Sales Competency Model. It is a comprehensive sales tool essential for all sales professionals--from those on the front line of selling, to those managing and developing sales talent, to those creating other sales enablement solutions. It provides guidance for customizing the model's key competencies for both organizations and individual sales professionals and features case studies, job aids, templates, and other tools critical for personal and organizational success. It offers key analysis of trends shaping today's sales ecosystem; presents detailed descriptions of sales competencies that drive success; describes how organizations and individuals can customize the new model to their own needs. --